Development of a set of plasmid vectors for genetic manipulations of the pathogenic yeast Candida parapsilosis - Kosa, Peter (2007)
A system for genetic transformation of the yeast Candida parapsilosis, recently developed in our laboratory, opened a venue for investigation of this pathogenic species at the molecular level. In this study we extend the range of available experimental tools by construction of a genomic DNA library suitable for screening and isolation of genes by functional complementation of yeast mutants and a set of replicative plasmid vectors for genetic manipulation of C. parapsilosis cells. The plasmids are based on auxotrophic (CpGAL1, CpURA3, CpMET2, CpLYS4) and dominant (CaIMH3) selection markers. In addition, we constructed plasmid derivatives containing reporter genes yEGFP3 and KlLAC4 coding for enhanced version of the green fluorescent protein and Kluyveromyces lactis β-galactosidase, respectively. The vectors facilitate propagation and expression of cloned genes in C. parapsilosis cells and allow intracellular localization of gene products and/or monitoring the activity of promoter sequences.